The Relationship of Population Growth to the Condition of Settlements in Tasikmalaya City - Irna Nuraeni; Ismi Oktapiani; Dina Akhira; Siti Fadjarajani; Cahya Darmawan (Program Studi Pendidikan Geografi Universitas Pattimura, 2026)
Population growth in urban areas has become one of the main factors influencing the condition of residential settlements. As a developing city, Tasikmalaya has experienced a significant increase in population due to urbanization and natural population growth. This study aims to analyze the relationship between population growth and the condition of community settlements in Tasikmalaya City, as well as its environmental impacts. The research employed a qualitative descriptive approach, with data collected through a literature review and secondary data analysis obtained from the Open Data of Tasikmalaya City and other relevant scientific sources. The findings indicate that population growth has increased the demand for residential land, leading to the emergence of slum settlements due to land scarcity and the imbalance between population growth and the provision of housing infrastructure. Slum areas in Tasikmalaya City were identified in several locations, including Purbaratu, Sukamenik, Mugarsari, and Tuguraja. These areas are characterized by high building density, limited access to clean water, inadequate drainage systems, poor waste management, and insufficient environmental facilities and infrastructure. The existence of slum settlements negatively affects both the physical environment and the social well-being of the community. Therefore, sustainable spatial planning, improvements in basic infrastructure, and stronger implementation of slum settlement management programs are essential to create livable and sustainable residential environments in Tasikmalaya City.